Impact of Phytophthora agathidicida infection on canopy and forest floor plant nutrient concentrations and fluxes in a kauri‐dominated forest. Issue 9 (19th March 2021) - Schwendenmann, Luitgard; Michalzik, Beate
Abstract: Kauri dieback, caused by Phytophthora agathidicida, is a biotic disturbance that poses a recent threat to the survival of kauri ( Agathis australis ) forests in New Zealand. Previous studies have shown that throughfall and stemflow play an important role in the kauri forests' internal nutrient cycle. However, the effects of P. agathidicida infection on canopy and forest floor nutrient fluxes in kauri forests remain unknown. Here, we measured throughfall, stemflow and forest floor water yield, nutrient (potassium, calcium, magnesium, manganese, silicon, sulfur, sodium, iron) concentrations and fluxes of ten kauri trees differing in soil P. agathidicida DNA concentration, and health status. We did not observe an effect of soil P. agathidicida DNA concentration on throughfall, stemflow, and forest floor water yield. Throughfall and forest floor nutrient concentrations and fluxes decreased (up to 50%) with increasing soil P. agathidicida DNA concentration. We found significant effects on potassium and manganese fluxes in throughfall; calcium and silicon fluxes in forest floor leachate. A decline in canopy and forest floor nutrient fluxes may result in soil nutrient imbalances, which in turn may negatively impact forest productivity and may increase the susceptibility of trees to future pathogen infection in these ecologically unique kauri forests. Given our findings and the increasing spread of Phytophthora species worldwide, research on the underlying physiological mechanisms linking dieback and plant–soil nutrient fluxes is critical. Abstract : First study on nutrient fluxes in a Phytophthora agathidicida ‐infected forest. Canopy and forest floor nutrient fluxes decreased with increasing P. agathidicida infection. Decline in plant nutrient supply may increase susceptibility to future pathogen infection.